2006
DOI: 10.1002/rcm.2430
|View full text |Cite
|
Sign up to set email alerts
|

New short peptaibols from a marine Trichoderma strain

Abstract: The production of peptaibols by a marine-related Trichoderma longibrachiatum strain was studied using electrospray ionisation multiple-stage ion trap mass spectrometry (ESI-MSn-IT) and gas chromatography/electron impact mass spectrometry (GC/EI-MS). Two major groups of peptaibols were identified, those with long sequences (20 amino acids) and others with short sequences (11 amino acids). This paper describes the methodology used to establish the sequences of short peptaibols in a mixture without previous indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…Methanol of HPLC quality grade was purchased from Baker (Deventer, Holland). Microheterogenous mixtures of peptaibols were sequenced using consecutive fragmentation in ESI-MS n , according to the method described previously (20,23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methanol of HPLC quality grade was purchased from Baker (Deventer, Holland). Microheterogenous mixtures of peptaibols were sequenced using consecutive fragmentation in ESI-MS n , according to the method described previously (20,23).…”
Section: Methodsmentioning
confidence: 99%
“…An extensive survey of 28 Trichoderma/Hypocrea species for peptaibol production by intact-cell MALDI-TOF mass spectrometry (ICMS) revealed that peptaibols are produced by all strains with some producing up to five peptide families of different sizes (19). In addition to terrestrial strains, peptaibols have also been isolated from marine strains of Trichoderma (7,20,22,23).…”
mentioning
confidence: 99%
“…The bioassay revealed that all examined isolates of T. viride, T. viridescens, T. asperellum, T. citrinoviride and T. longibrachiatum have bioactive compounds in their crude extracts. Peptaibols have the same chemical characteristics and molecular masses, therefore they cannot be completely separated by HPLC and are eluted together [28]. The complete separation of peptaibols is usually difficult but certain methods such as high energy collision, or collision-induced dissociation mass spectrometry were applicable to characterize peptaibols in crude extracts [34].…”
Section: Discussionmentioning
confidence: 99%
“…The complete separation of peptaibols is usually difficult but certain methods such as high energy collision, or collision-induced dissociation mass spectrometry were applicable to characterize peptaibols in crude extracts [34]. The ESI-IT-MS technology is a more simple method for the sequencing of peptaibols [28]. We used HPLC for separation and ESI-MS for sequencing and identification of peptaibol compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Selective inhibitory activity against PTEN-negative MDA468 tumor cells has been observed [187]. Furthermore, eight new eleven-residue peptaibols, trichobrachins A I -IV and B I -IV, as well as one trichorovin [110] were reported from T. longibrachiatum MMS 151, a marine strain that has been isolated from the cockle Mytilus edulis [188].…”
mentioning
confidence: 95%